"You have to take action": changing knowledge and attitudes towards newborn care practices during crisis in South Sudan. Issue 51 (30th November 2017) - Sami, Samira; Kerber, Kate; Tomczyk, Barbara; Amsalu, Ribka; Jackson, Debra; Scudder, Elaine; Dimiti, Alexander; Meyers, Janet; Kenneth, Kemish; Kenyi, Solomon; Kennedy, Caitlin E.; Ackom, Kweku; et al.
Abstract: Highest rates of neonatal mortality occur in countries that have recently experienced conflict. International Medical Corps implemented a package of newborn interventions in June 2016, based on the Newborn health in humanitarian settings: field guide, targeting community- and facility-based health workers in displaced person camps in South Sudan. We describe health workers' knowledge and attitudes toward newborn health interventions, before and after receiving clinical training and supplies, and recommend dissemination strategies for improved uptake of newborn guidelines during crises. A mixed methods approach was utilised, including pre–post knowledge tests and in-depth interviews. Study participants were community- and facility-based health workers in two internally displaced person camps located in Juba and Malakal and two refugee camps in Maban from March to October 2016. Mean knowledge scores for newborn care practices and danger signs increased among 72 community health workers (pre-training: 5.8 [SD: 2.3] vs. post-training: 9.6 [SD: 2.1]) and 25 facility-based health workers (pre-training: 14.2 [SD: 2.7] vs. post-training: 17.4 [SD: 2.8]). Knowledge and attitudes toward key essential practices, such as the use of partograph to assess labour progress, early initiation of breastfeeding, skin-to-skin care and weighing the baby, improved among skilled birth attendants. Despite challenges in conflict-affected settings, conducting training has the potential to increase health workers' knowledge on neonatal health post-training. The humanitarian community should reinforce this knowledge with key actions to shift cultural norms that expand the care provided to women and their newborns in these contexts.